Genome Biology - Berghe, Veronique; SpringerLink (Online service) (London : BioMed Central : Imprint: BioMed Central.)
Genome Biology covers all areas of biology and biomedicine studied from a genomic and post-genomic perspective. Content includes research, new methods and software tools, and reviews. Areas covered include, but are not limited to: sequence analysis; bioinformatics; insights into molecular, cellular and organismal biology; functional genomics; epigenomics; population genomics; proteomics; comparative biology and evolution; systems and network biology; genome editing and engineering; genomics of disease; and clinical genomics. All content is open access immediately on publication.
Keywords: Genetics; Epigenetics; Bioinformatics; Plant genetics; Microbial genetics; Evolution (Biology).; Genetics and Genomics; Epigenetics; Bioinformatics; Plant Genetics; Microbial Genetics; Evolutionary Biology